Sensitivity of a spatially-varying Elastic Lithosphere-Relaxed Asthenosphere (ELRA) isostatic model of the Antarctic ice sheet - Coulon, Violaine; Pattyn, Frank (2018)
On glacial-interglacial time scales, isostatic effects of ice sheet volume changes may have a large impact on timingand magnitude of retreating and advancing ice through grounding-line migration. A common isostatic model usedin ice-flow modelling is the Elastic Lithosphere-Relaxed Asthenosphere (ELRA) model. It considers an elasticlithosphere, defined by a given effective lithosphere thickness and a relaxation equation for asthenospheric responsewith a characteristic time scale as a function of asthenosphere viscosity. However, effective lithosphere thicknessin Antarctica ranges from tens (West-Antarctica) to hundreds of meters (East Antarctica), leading to a flexuralrigidity that varies spatially across several orders of magnitude. Furthermore, recent studies also point out to alarge spatial variability in asthenosphere viscosity. Here, we explore in a sensitivity analysis both spatially uniformand spatially varying values of flexural rigidity and asthenosphere viscosity applied to a model of the Antarcticice sheet, forced by background temperature and sea-level changes over the last 40,000 years, thus covering thelast glacial-interglacial transition. Results demonstrate a higher sensitivity for the West Antarctic ice sheet, whereasthenosphere viscosity essentially influences timing and magnitude of grounding-line retreat during the glacialinterglacialtransition. info:eu-repo/semantics/published